2013
DOI: 10.1136/bjophthalmol-2012-302666
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic unilateral retinoblastoma or first sign of bilateral disease?

Abstract: This study shows that an oncogenic RB1 mutation in the blood is a risk factor for metachronous bilateral retinoblastoma. Additional clinical risk factors for metachronous bilateral disease are diagnosis at young age (≤0.5 years) and multifocal unilateral retinoblastoma. Early genetic analysis may identify children at high risk of developing metachronous bilateral disease and may help to preserve vision using risk-adapted follow-up and early treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
12
2
Order By: Relevance
“…Sequential, contralateral eye involvement in our group of patients was always Group A disease, which was amenable to treatment with focal modalities without a significant loss of vision. Several authors have previously reported that approximately 20% of patients before 6 months of age with unilateral disease eventually became bilateral patients [2,16]. Abramson et al [2] recommended that this factor should be considered when making treatment decisions at diagnosis, but we found unconvincing evidence for this treatment concept in our series.…”
Section: Discussioncontrasting
confidence: 55%
“…Sequential, contralateral eye involvement in our group of patients was always Group A disease, which was amenable to treatment with focal modalities without a significant loss of vision. Several authors have previously reported that approximately 20% of patients before 6 months of age with unilateral disease eventually became bilateral patients [2,16]. Abramson et al [2] recommended that this factor should be considered when making treatment decisions at diagnosis, but we found unconvincing evidence for this treatment concept in our series.…”
Section: Discussioncontrasting
confidence: 55%
“…They detected six low-level mosaic mutations in bilateral Rb and four in unilateral Rb, increasing their detection rate from 96% to 97% for bilateral Rb and from 13% to 18% for unilateral Rb. Since the detection of germline mosaicism has important clinical consequences for the patient and family members as has been pointed out in many papers,26 39 the ultimate goal remains to detect all RB1 mutations, both in the tumour and the germline.…”
Section: Discussionmentioning
confidence: 99%
“…Messmer 40 quantified and found delays of ≥120 days to be statistically significant for the development of metastatic retinoblastoma. Patients presenting with glaucoma and/or buphthalmia have significantly elevated pathologic risk factors, including those resulting in microscopically residual disease and optic nerve invasion 33,41,42…”
Section: High Risks In Retinoblastomamentioning
confidence: 99%